Adhesive composition
Patent Information
- Application Number
- CN202580023765.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-26
- Filing Date
- 2025-03-04
- Publication Date
- 2026-10-27
AI Technical Summary
[0019]本发明的粘合剂组合物在低温区域中的耐弯曲性优异,且不易随着时间的推移而产生白浊。
Smart Images

Figure CN122996145A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to adhesive compositions. Background Technology
[0002] In recent years, image display devices such as liquid crystal displays (LCDs) and organic OLED displays (OLEDs) have been widely used in various fields, along with touch panels incorporating touch sensors. These image display devices and touch panels have structures in which various optical components, such as polarizing films, phase retardation films, optical compensation films, touch sensor films, and cover films, are stacked on the image display panel. In applications where these optical components are bonded, adhesive sheets with adhesive layers are used. For example, in bonding various optical components in an image display device, optical adhesive sheets are used (see, for example, Patent Documents 1 to 3).
[0003] On the other hand, for example, in applications such as smartphones and tablet terminals, there is ongoing development of display panels that can be repeatedly bent (foldable). Specifically, foldable display panels can repeatedly deform between a curved shape and a flat, non-curved shape. In such foldable display panels, the components in the stacked structure are manufactured in a manner that allows for repeated bending, and thin optical adhesive sheets are used to join these components. Optical adhesive sheets for flexible devices such as foldable display panels are described, for example, in Patent Document 4 below.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-238915
[0007] Patent Document 2: Japanese Patent Application Publication No. 2003-342542
[0008] Patent Document 3: Japanese Patent Application Publication No. 2004-231723
[0009] Patent Document 4: Japanese Patent Application Publication No. 2018-111754 Summary of the Invention
[0010] The problem that the invention aims to solve
[0011] For adhesive sheets used in flexible devices operating in low-temperature regions, high flexural strength is required even at low temperatures. However, conventional adhesive sheets with excellent flexural strength in low-temperature regions sometimes develop clouding over time, impairing the optical properties of devices such as displays. Therefore, adhesive sheets that exhibit excellent flexural strength in low-temperature regions and are less prone to clouding over time are sometimes required.
[0012] The present invention addresses the problem of providing an adhesive composition that exhibits excellent flexural strength in low-temperature regions and is resistant to clouding over time.
[0013] means for solving problems
[0014] This invention provides an adhesive composition, wherein the adhesive composition has a shear storage modulus (G') of less than 60 kPa at -20°C. Regarding a laminate obtained by bonding two pieces of glass together using the adhesive composition, after a damp heat test at 65°C and 90% RH for 500 hours, the difference ΔHz between the post-damp heat test haze value and the initial haze value before the damp heat test [post-damp heat test haze value (%) - initial haze value (%)] is less than 2%.
[0015] Preferably, the shear storage modulus (G') of the above-mentioned adhesive composition at 25°C is 40 kPa or less.
[0016] Preferably, the initial haze value is greater than 0.01% and less than 3%, and the haze value after the damp heat test is greater than 0.01% and less than 4%.
[0017] Preferably, the dielectric constant of the above adhesive composition at a frequency of 100 kHz is 4.0 or less.
[0018] Invention Effects
[0019] The adhesive composition of the present invention exhibits excellent flexural strength in low-temperature regions and is not prone to clouding over time. Attached Figure Description
[0020] Figure 1 This is a schematic diagram (cross-sectional view) illustrating one embodiment of the adhesive sheet of the present invention. Detailed Implementation
[0021] [Adhesive Composition]
[0022] The shear storage modulus (G') of the adhesive composition of the present invention at -20°C is 60 kPa or less, preferably 55 kPa or less, and more preferably 50 kPa or less. With a shear storage modulus of 60 kPa or less, the adhesive sheet exhibits high flexibility and excellent bending resistance in the low-temperature region. Furthermore, from the viewpoint of ensuring the cohesiveness of the adhesive sheet in the low-temperature region, the shear storage modulus (G') at -20°C is preferably 30 kPa or more, more preferably 35 kPa or more, and even more preferably 40 kPa or more.
[0023] From the viewpoint of ensuring flexible deformability that can follow the height of the adhered object when it deforms, the shear storage modulus (G') of the adhesive composition of the present invention at 25°C is preferably 40 kPa or less, more preferably 35 kPa or less, and even more preferably 30 kPa or less. Furthermore, the shear storage modulus (G') at 25°C is preferably 4 kPa or more, more preferably 8 kPa or more, and even more preferably 10 kPa or more.
[0024] The shear storage modulus (G') at -20°C and the shear storage modulus (G') at 25°C can be obtained by measuring the adhesive layer formed from the above adhesive composition. Furthermore, the shear storage modulus (G') at -20°C and the shear storage modulus (G') at 25°C can be adjusted by modifying the type of base polymer constituting the adhesive composition, monomer composition, molecular weight of the base polymer, and the type and content of additives such as crosslinking agents.
[0025] Regarding the adhesive composition of the present invention, for a laminate obtained by bonding two pieces of glass together using the adhesive composition, the difference ΔHz [post-damp heat test haze value (%) - initial haze value (%)] between the laminate after a damp heat test at 65°C and 90% RH for 500 hours and the laminate before the damp heat test (sometimes called the initial haze value) is less than 2%, preferably less than 1%, more preferably less than 0.7%, and even more preferably less than 0.5%. With ΔHz less than 2%, the adhesive composition is less prone to clouding over time, and the optical properties of devices such as displays using the adhesive composition are less likely to be damaged.
[0026] From the viewpoint that devices such as displays using the above-described adhesive composition have superior optical properties, the initial haze value is preferably less than 3%, more preferably less than 2%, further preferably less than 1%, and particularly preferably less than 0.5%. Alternatively, the initial haze value may be greater than 0.01%, or greater than 0.03%, greater than 0.05%, or greater than 0.07%.
[0027] From the viewpoint that devices such as displays using the above-described adhesive composition exhibit superior optical properties over time, the haze value after the above-described damp heat test is preferably less than 4%, more preferably less than 3%, further preferably less than 2%, and particularly preferably less than 1%. Additionally, the haze value after the above-described damp heat test may be greater than 0.01%, or may be greater than 0.03%, greater than 0.05%, or greater than 0.07%.
[0028] The haze value of the glass used in measuring the initial haze value and the haze value after the damp heat test is preferably 0.15% or less. The initial haze value and the haze value after the damp heat test can be obtained by measuring the adhesive layer formed from the adhesive composition. Furthermore, the initial haze value and the haze value after the damp heat test can be adjusted by modifying the type of base polymer constituting the adhesive composition, the monomer composition, and the type and content of additives such as crosslinking agents.
[0029] From the viewpoint of suppressing device malfunctions, the dielectric constant of the adhesive composition of the present invention at a frequency of 100 kHz is preferably 4.0 or less, more preferably 3.5 or less, and even more preferably 3.0 or less. Furthermore, from the viewpoint of improving the sensitivity of the touch sensor (especially a capacitive touch sensor), it is preferably 1.5 or more, more preferably 2.0 or more, and may also be 2.1 or more or 2.2 or more.
[0030] The dielectric constant of the adhesive composition of the present invention at a frequency of 100 kHz can be adjusted by regulating the type of base polymer constituting the adhesive composition, monomer composition, type and content of additives, etc. It should be noted that in this specification, "dielectric constant" and "relative dielectric constant" are considered synonymous.
[0031] The adhesive composition of the present invention can have any form, for example, solvent-based, emulsion-based, hot-melt (thermal melt), solvent-free, etc. Solvent-free adhesive compositions do not require a step of removing the solvent by evaporation from the coating film during the manufacturing process of the adhesive layer from the composition. Therefore, adhesive sheets having an adhesive layer formed from the adhesive composition of the present invention are suitable for reducing environmental impact.
[0032] The adhesive composition of the present invention preferably contains one or more of the group consisting of a base polymer, a monomer composition constituting the base polymer, and a portion of the polymer of the monomer composition.
[0033] The monomer composition described above may consist of a single polymerizable component or may be a mixture of polymerizable components containing two or more polymerizable components. Furthermore, the aforementioned partial polymer is a composition obtained by partially polymerizing one or more polymerizable components of the monomer composition described above. Additionally, in this specification, the term "base polymer" generally includes, unless otherwise specified, "base polymer," "monomer composition constituting the base polymer," and "partial polymer of the monomer composition."
[0034] There are no particular limitations on the base polymers mentioned above. Examples include: acrylic polymers in acrylic adhesive compositions, rubber polymers in rubber adhesive compositions (natural rubber adhesive compositions, synthetic rubber adhesive compositions, etc.), polysiloxane polymers in polysiloxane adhesive compositions, polyester polymers in polyester adhesive compositions, urethane polymers in urethane adhesive compositions, polyamide polymers in polyamide adhesive compositions, epoxy polymers in epoxy adhesive compositions, vinyl alkyl ether polymers in vinyl alkyl ether adhesive compositions, and fluorinated polymers in fluorinated adhesive compositions. Only one of the above base polymers may be used, or two or more may be used.
[0035] The aforementioned base polymer is the adhesive component that exhibits adhesive properties in the adhesive layer. The base polymer is preferably an acrylic polymer. An acrylic polymer is a (co)polymer containing a polymerizable component of (meth)acrylate in a proportion of 50% by mass or more. "(Meth)acrylate" refers to acrylic acid and / or methacrylic acid. Only one type of (meth)acrylate may be used, or two or more types may be used.
[0036] The ester moiety of (meth)acrylates can be either linear or branched, and can also have cyclic hydrocarbon groups such as alicyclic alkyl groups. From the viewpoint of more easily achieving both low shear storage modulus and low ΔHz at -20°C, (meth)acrylates preferably include those with a branched ester moiety. It should be noted that, in this specification, "branched" refers to a structure in which the ester moiety has branching points and the branches do not bond together to form a ring. For example, (meth)acrylates having only one alicyclic hydrocarbon group, such as cyclohexyl methacrylate, are not included in (meth)acrylates with a "branched" ester moiety.
[0037] In (meth)acrylates where the ester moiety is branched, it is preferable to use oxygen atoms ("-C(=O") from the ester bond. 1 )-O 2 The "O" in "-" 2 The first to fourth atoms (preferably carbon atoms) of the ester portion, counting from the oxygen atom in the ester bond, have branch points. That is, the first to fourth carbon atoms, counting from the oxygen atom in the ester bond, are preferably tertiary carbon atoms or quaternary carbon atoms (preferably tertiary carbon atoms).
[0038] In this specification, the chain with the most atoms constituting the ester moiety is sometimes referred to as the "main chain," and the chain bonded to the atoms constituting the main chain but not included in the main chain is sometimes referred to as a "side chain." Furthermore, the hydrocarbon-containing chain bonded to the branch point is sometimes referred to as a "branch." One of the branches is part of the main chain, and the others are side chains. The main chain comprises the chain from the oxygen atom in the ester bond to the branch point and one branch. The number of branches bonded to the branch point is two or more, preferably two.
[0039] In branched (meth)acrylates where the ester portion is branched, the number of atoms in at least two of the two or more branches is preferably 4 or more, more preferably 5 or more, and even more preferably 6 or more. Furthermore, the number of atoms in the chains constituting the aforementioned two or more branches is, for example, 12 or less, preferably 10 or less. The number of atoms constituting the aforementioned at least two chains may be the same or different.
[0040] In this specification, a (meth)acrylate having an ester moiety of the following characteristics is sometimes referred to as "(meth)acrylate (A)": the ester moiety has two or more branches on the first to fourth atom (preferably a carbon atom) counting from the oxygen atom in the ester bond, and the number of atoms constituting at least two of the two or more branches is four or more. The use of (meth)acrylate (A) makes it easier to achieve a balance between low shear storage modulus and low ΔHz at -20°C. In this specification, the term "number of atoms constituting the chain" refers to the number of atoms constituting only the chain, for example, the total number of carbon atoms in the hydrocarbon group when the main chain or branches are hydrocarbon groups with ether bonds, and the total number of carbon atoms and oxygen atoms in the hydrocarbon group with ether bonds when the main chain or branches are hydrocarbon groups with ether bonds. Such a configuration makes it easier to achieve a balance between low shear storage modulus and low ΔHz at -20°C. The number of branches in the ester moiety of (meth)acrylate (A) is preferably two.
[0041] The number of atoms (total) of the chains constituting the ester moiety of (meth)acrylate (A) is 9 or more, preferably 12 or more, and more preferably 14 or more. Furthermore, the number of atoms (total) of the chains constituting the ester moiety of (meth)acrylate (A) is preferably 24 or less, more preferably 22 or less, and even more preferably 20 or less. This configuration makes it easier to achieve a balance between low shear storage modulus and low ΔHz at -20°C.
[0042] In the ester portion of (meth)acrylate (A), the difference between the number of atoms constituting the main chain and the number of atoms constituting the corresponding side chains [number of atoms constituting the main chain - number of atoms constituting the side chains] is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more. Furthermore, the difference is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less. This configuration makes it easier to achieve a balance between low shear storage modulus and low ΔHz at -20°C.
[0043] In the ester moiety of (meth)acrylate (A), the atoms constituting the aforementioned branch chain are preferably only carbon atoms, or carbon atoms and oxygen atoms. The aforementioned branch chain is preferably a hydrocarbon group that may have an alkoxy group, more preferably a hydrocarbon group, and even more preferably an aliphatic hydrocarbon group.
[0044] In the ester moiety of (meth)acrylate (A), the atoms constituting the main chain are preferably only carbon atoms, or carbon atoms and oxygen atoms. The main chain is preferably a hydrocarbon group that may have an alkoxy group, more preferably a hydrocarbon group, and even more preferably an aliphatic hydrocarbon group.
[0045] The (meth)acrylate (A) is preferably composed of one or more (preferably two or more) side chains consisting of only carbon atoms, or carbon atoms and oxygen atoms. The aforementioned one or more (preferably two or more) side chains are preferably hydrocarbon groups having alkoxy groups, more preferably hydrocarbon groups, and even more preferably aliphatic hydrocarbon groups.
[0046] Examples of (meth)acrylates (A) include: branched (meth)acrylate alkyl esters, (meth)acrylate alkoxyalkyl esters, (meth)acrylate poly(oxyalkylene) esters, etc.
[0047] Examples of alkyl methacrylates mentioned above include 2-hexyldecyl methacrylate.
[0048] (Meth)acrylate (A) is preferably a branched alkyl (meth)acrylate, more preferably a branched alkyl (meth)acrylate having 9 to 24 carbon atoms, and even more preferably 2-hexyldecyl (meth)acrylate (2HDA). For example, in the case of 2-hexyldecyl (meth)acrylate, the oxygen atom in the ester bond (the aforementioned "O")... 2 The second carbon atom, starting from the first carbon atom, has a branch point, and at the branch point there are 8 hydrocarbon groups forming the chain and 6 hydrocarbon groups forming the chain. The number of atoms forming the main chain is 10, the number of atoms forming the side chain is 6, and [number of atoms forming the main chain - number of atoms forming the side chain] is 4.
[0049] From the viewpoint of more easily achieving a balance between low shear storage modulus and low ΔHz at -20°C, the proportion of (meth)acrylate (A) relative to the total amount (100% by mass) of the polymerizable components constituting the above-mentioned basic polymer is preferably 15% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, and can be 30% by mass or more, 35% by mass or more, 40% by mass or more, or 45% by mass or more, particularly preferably 50% by mass or more. The above proportion is preferably 99% by mass or less, more preferably 98% by mass or less, even more preferably 97% by mass or less, and can be 96% by mass or less, 95% by mass or less, 93% by mass or less, or 90% by mass or less.
[0050] In addition, (meth)acrylates can be used together with (meth)acrylate (A) in combination with other (meth)acrylates other than (meth)acrylate (A), such as alkyl (meth)acrylates having branched alkyl groups with 8 or fewer carbon atoms (preferably 4 to 8 carbon atoms) and alkyl (meth)acrylates having straight-chain alkyl groups with 9 to 24 carbon atoms. Only one of the aforementioned other alkyl (meth)acrylates may be used, or two or more may be used.
[0051] Other alkyl methacrylates mentioned above include, for example: methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, pentyl methacrylate, isoamyl methacrylate, neopentyl methacrylate, hexyl methacrylate, heptyl methacrylate, 2-ethylhexyl methacrylate, octyl methacrylate, isooctyl methacrylate, nonyl methacrylate, isononyl methacrylate, decyl methacrylate, isodecanyl methacrylate, undecyl methacrylate, dodecyl methacrylate (i.e., lauryl methacrylate), isotridecyl methacrylate, tetradecyl methacrylate, isotetradecyl methacrylate, pentadecyl methacrylate, cetyl methacrylate, heptadecanyl methacrylate, hexadecyl methacrylate, octadecyl methacrylate, isostearyl methacrylate, and nonadecanyl methacrylate.
[0052] In addition, other alkyl methacrylates mentioned above can be listed as alkyl methacrylates having an alicyclic alkyl group. Examples of alkyl methacrylates having an alicyclic alkyl group include: cycloalkyl methacrylates, alkyl methacrylates having a bicyclic aliphatic hydrocarbon ring, and alkyl methacrylates having three or more aliphatic hydrocarbon rings. Examples of cycloalkyl methacrylates include: cyclopentyl methacrylate, cyclohexyl methacrylate, cycloheptyl methacrylate, and cyclooctyl methacrylate. Examples of alkyl methacrylates having a bicyclic aliphatic hydrocarbon ring include: isobornyl methacrylate. Examples of alkyl methacrylates having three or more aliphatic hydrocarbon rings include: tetrahydrodicyclopentadienyl methacrylate, tetrahydrodicyclopentadienyloxyethyl methacrylate, tetrahydrotricyclopentadienyl methacrylate, 1-adamantyl methacrylate, 2-methyl-2-adamantyl methacrylate, and 2-ethyl-2-adamantyl methacrylate.
[0053] Furthermore, the aforementioned other alkyl methacrylates may have one or more alkoxy groups. Examples of alkyl methacrylates containing alkoxy groups include: 2-methoxymethyl methacrylate, 2-methoxyethyl methacrylate, 2-methoxybutyl methacrylate, ethyl carbitol (meth)acrylate (ethoxyethoxyethyl methacrylate), 2-ethylhexyl carbitol (meth)acrylate, etc.
[0054] From the viewpoint of appropriately exhibiting basic properties such as adhesion in the adhesive sheet, the total proportion of (meth)acrylate (A) and the other (meth)acrylate alkyl esters mentioned above is preferably 55% by mass or more, more preferably 60% by mass or more, and even more preferably 80% by mass or more, relative to the total amount (100% by mass) of the polymerizable components in the above adhesive composition. The above total proportion is preferably 99% by mass or less, more preferably 98% by mass or less, even more preferably 97% by mass or less, and may also be 96% by mass or less, 95% by mass or less, 93% by mass or less, or 90% by mass or less.
[0055] The polymerizable component described above may include copolymerizable monomers capable of copolymerizing with (meth)acrylate (A) and alkyl (meth)acrylate. Examples of such copolymerizable monomers include monomers having polar groups. Examples of such polar monomers include hydroxyl-containing monomers, carboxyl-containing monomers, and monomers having nitrogen-containing rings. These polar monomers facilitate the modification of acrylic polymers, such as introducing crosslinking points and ensuring the cohesiveness of the acrylic polymers. Only one or more of the aforementioned copolymerizable monomers may be used.
[0056] Examples of hydroxyl-containing monomers include: 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl methacrylate, 8-hydroxyoctyl methacrylate, 10-hydroxydecyl methacrylate, and 12-hydroxylaurate methacrylate, etc., which are hydroxyalkyl methacrylates.
[0057] As the aforementioned monomer containing a polar group, a hydroxyl-containing monomer is preferred, and a hydroxyalkyl ester of (meth)acrylate is more preferred. From the viewpoint that it is easier to achieve both low shear storage modulus and low ΔHz at -20°C, a hydroxyalkyl ester of (meth)acrylate with 3 or more carbon atoms (e.g., 3 to 8) in the alkyl group is even more preferred, and 4-hydroxybutyl acrylate (4HBA) is particularly preferred.
[0058] From the viewpoint of achieving low ΔHz, introducing cross-linking structures into acrylic polymers, and ensuring cohesion in the adhesive layer, the proportion of hydroxyl-containing monomers is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, relative to the total amount (100% by mass) of the polymerizable components constituting the aforementioned base polymer. From the viewpoint of achieving a low shear storage modulus at -20°C, the aforementioned proportion is preferably 50% by mass or less, and can be 45% by mass or less, 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, 20% by mass or less, or 15% by mass or less.
[0059] Examples of carboxyl-containing monomers include: acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0060] From the viewpoint of introducing a cross-linking structure into the acrylic polymer, ensuring cohesiveness in the adhesive layer, and ensuring adhesion of the adhesive layer to the adherend, the proportion of carboxyl-containing monomers is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, relative to the total amount (100% by mass) of the polymerizable components constituting the base polymer. From the viewpoint of adjusting the glass transition temperature of the acrylic polymer and avoiding the risk of corrosion of the adherend due to acid, the above proportion is preferably 3% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less.
[0061] Examples of monomers having a nitrogen-containing ring include: N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrrazine, N-vinylpyrrole, N-vinylimidazolium, N-vinylpyrazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-pyrazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisopyrazole, N-vinylthiazole, and N-vinylisothiazole.
[0062] The proportion of monomers having nitrogen-containing atomic rings is, for example, 0.5% by mass or more, and can be 1% by mass or more, or 1.5% by mass or more, relative to the total amount (100% by mass) of the polymerizable components constituting the above-mentioned basic polymer. From the viewpoint that it is easier to achieve both low shear storage modulus and low ΔHz at -20°C, the above-mentioned proportion is preferably 10% by mass or less, more preferably 7% by mass or less, further preferably 5% by mass or less, even more preferably 1% by mass or less, particularly preferably 0.5% by mass or less, and can be substantially non-existent. In the above-mentioned adhesive composition, "substantially non-existent" means that monomers having nitrogen-containing atomic rings are not actively incorporated, except in cases where monomers having nitrogen-containing atomic rings are inevitably mixed in.
[0063] The polymerizable component described above may contain other copolymerizable monomers. Examples of such other copolymerizable monomers include: acid anhydride monomers, sulfonic acid monomers, phosphate monomers, epoxy monomers, cyano monomers, and aromatic vinyl compounds. Only one of these other copolymerizable monomers may be used, or two or more may be used.
[0064] The adhesive composition described above may contain polymerization initiators such as photopolymerization initiators. The base polymer described above can be formed, for example, by photopolymerizing the polymerizable components described above. One or more photopolymerization initiators may be used.
[0065] Examples of photopolymerization initiators include: free radical photopolymerization initiators, cationic photopolymerization initiators, and anionic photopolymerization initiators.
[0066] Examples of free radical photopolymerization initiators include: acylphosphine oxide photopolymerization initiators, benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-keto alcohol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzoyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, and thioxanone photopolymerization initiators.
[0067] Examples of acylphosphine oxide photopolymerization initiators include: bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of benzoin ether photopolymerization initiators include: benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-1,2-diphenylethane-1-one. Examples of acetophenone photopolymerization initiators include: 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of α-keto alcohol polymerization initiators include 2-methyl-2-hydroxyphenylacetone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride photopolymerization initiators include 2-naphthalenesulfonyl chloride. Examples of photoactive oxime photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(O-ethoxycarbonyl)-oxime. Examples of benzoin photopolymerization initiators include benzoin. Examples of benzoyl photopolymerization initiators include benzoyl. Examples of benzophenone photopolymerization initiators include benzoyl. Examples of benzophenone photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, and poly(vinylbenzophenone). Examples of ketal photopolymerization initiators include benzoyl dimethyl ketal. Examples of photopolymerization initiators for thioxanthone include: thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0068] The aforementioned photopolymerization initiator is preferably at least one selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,2-dimethoxy-1,2-diphenylethane-1-one, and 1-hydroxycyclohexylphenyl ketone.
[0069] Relative to the total amount of polymerizable components (100 parts by mass), the amount of the aforementioned photopolymerization initiator (the total amount of multiple photopolymerization initiators when multiple photopolymerization initiators are used) is, for example, 0.01 parts by mass or more, preferably 0.03 parts by mass or more, more preferably 0.05 parts by mass or more, and for example, 1 part by mass or less, preferably 0.5 parts by mass or less, more preferably 0.3 parts by mass or less, and even more preferably 0.2 parts by mass or less.
[0070] The adhesive composition described above may contain a crosslinking agent. By using the crosslinking agent, the base polymer will have a crosslinked structure. Examples of methods for introducing a crosslinked structure into the base polymer include the following first and second methods. In the first method, a base polymer having functional groups capable of reacting with the crosslinking agent and a crosslinking agent are incorporated into the adhesive composition, and the base polymer and the crosslinking agent react in the adhesive layer. In the second method, a multifunctional compound (crosslinking agent) such as a multifunctional monomer is included along with a polymerizable component, and through the polymerization of this polymerizable component, a base polymer with a branched structure (crosslinked structure) introduced into the polymer chain is formed. These methods can be used in combination.
[0071] Examples of crosslinking agents used in the first method described above include compounds that react with polar groups (hydroxyl and carboxyl groups, etc.) in monomers having polar groups. Examples of such crosslinking agents include isocyanate crosslinking agents, peroxide crosslinking agents, epoxy crosslinking agents, α-azoline crosslinking agents, aziridine crosslinking agents, carbodiimide crosslinking agents, and metal chelate crosslinking agents. Only one crosslinking agent may be used, or two or more may be used.
[0072] From the viewpoint of ensuring the cohesiveness of the adhesive layer, the amount of crosslinking agent in the first method is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and even more preferably 0.05 parts by mass or more, and preferably 3 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.5 parts by mass or less, relative to 100 parts by mass of the total amount of polymerizable components (or the total amount of the base polymer).
[0073] In the second method described above, monofunctional monomers and polyfunctional compounds, such as polyfunctional monomers used to introduce crosslinking structures, can be polymerized in a single step or in multiple steps. In the multi-step polymerization method, firstly, a prepolymer composition containing a portion of the polymer (a mixture of low-degree polymers and unreacted monomers) is prepared by polymerizing the monofunctional monomer (prepolymerization). Next, a polyfunctional compound is added to the prepolymer composition as a crosslinking agent, and then the portion of the polymer is polymerized with the polyfunctional compound (main polymerization).
[0074] Examples of multifunctional compounds include polyfunctional monomers and polyfunctional oligomers that contain two or more olefinic unsaturated double bonds in one molecule. Examples of polyfunctional monomers include polyfunctional (meth)acrylates.
[0075] Examples of polyfunctional (meth)acrylates include: difunctional (meth)acrylates, trifunctional (meth)acrylates, and polyfunctional (meth)acrylates with more than four functions.
[0076] Examples of bifunctional (meth)acrylates include: ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, glycerol dimethacrylate, ethoxylated bisphenol A dimethacrylate (BPAEODE), and neopentyl glycol dimethacrylate.
[0077] Examples of trifunctional (meth)acrylates include: trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tri(acryloyloxyethyl) isocyanurate.
[0078] Examples of polyfunctional (meth)acrylates with more than four functions include: di(trimethylolpropane)tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, alkyl-modified dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0079] Examples of multifunctional oligomers include: urethane (meth)acrylate oligomers, polyester (meth)acrylate oligomers, polyether (meth)acrylate oligomers, polyol (meth)acrylate oligomers, epoxy (meth)acrylate oligomers, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate.
[0080] The multifunctional compound used as the crosslinking agent in the second method can be used alone or in combination with two or more. Preferably, at least one compound selected from the group consisting of 1,6-hexanediol diacrylate (HDDA) and dipentaerythritol hexaacrylate (DPHA) is used.
[0081] When using a multifunctional monomer as the multifunctional compound, from the viewpoint of ensuring the cohesiveness of the adhesive layer, the amount of the multifunctional monomer is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and even more preferably 0.05 parts by mass or more, relative to 100 parts by mass of the total amount of the monofunctional monomer. From the viewpoint of ensuring the flexibility and deformability of the adhesive layer, the amount of the multifunctional monomer is preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1 part by mass or less, relative to 100 parts by mass of the total amount of the monofunctional monomer.
[0082] When using a multifunctional oligomer as the multifunctional compound, from the viewpoint of ensuring the cohesiveness of the adhesive layer, the amount of the multifunctional oligomer in the polymerizable component is preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.7 parts by mass or more, relative to 100 parts by mass of the total monofunctional monomer. From the viewpoint of ensuring the flexibility and deformability of the adhesive layer, the amount of the multifunctional oligomer is preferably 8 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, relative to 100 parts by mass of the total monofunctional monomer.
[0083] In polymerization, chain transfer agents can be used to adjust molecular weight, etc. That is, the above-mentioned adhesive composition may contain a chain transfer agent. Examples of chain transfer agents include: α-thioglycerol, lauryl thiol, glycidyl thiol, mercaptoacetic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl mercaptoacetic acid, 2,3-dimercapto-1-propanol, and α-methylstyrene dimer. Only one chain transfer agent may be used, or two or more may be used.
[0084] The adhesive composition described above may contain a silane coupling agent. The content of the silane coupling agent is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, relative to 100 parts by mass of the total polymerizable components (or the total amount of the base polymer). The content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less.
[0085] The adhesive composition described above may contain other components besides those listed above, without impairing the effects of the present invention. Examples of such other components include: curing agents, curing catalysts, crosslinking accelerators, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenolic resins, etc.), anti-aging agents, fillers (metal powders, organic fillers, inorganic fillers, etc.), colorants (pigments or dyes, etc.), antioxidants, plasticizers, softeners, surfactants, antistatic agents, surface lubricants, leveling agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, rust inhibitors, granules, foils, flame retardants, ion traps, etc. Only one of the above-mentioned components may be used, or two or more may be used.
[0086] The adhesive composition described above is preferably solvent-free. That is, the adhesive composition preferably does not contain or substantially does not contain organic solvents. As for the organic solvent, there are no particular limitations on any organic compound that can be used as a solvent, such as: hydrocarbon solvents like cyclohexane, hexane, and heptane; aromatic solvents like toluene and xylene; ester solvents like ethyl acetate and methyl acetate; ketone solvents like acetone and methyl ethyl ketone; and alcohol solvents like methanol, ethanol, butanol, and isopropanol. It should be noted that the organic solvent described above can be a mixture containing two or more organic solvents.
[0087] In the above-mentioned adhesive composition, "substantially free" organic solvent means that, except in cases where organic solvent is unavoidably mixed in, no organic solvent is actively incorporated. Specifically, the proportion of organic solvent in the adhesive composition relative to the total amount of the adhesive composition (total mass, 100% by mass) is said to be substantially free, which is 1.0% by mass or less (preferably 0.5% by mass or less, more preferably 0.2% by mass or less).
[0088] The above-described adhesive compositions can be prepared by known or conventional methods. For example, the solvent-free adhesive compositions can be prepared by adding additives as needed to a mixture of polymerizable components or a portion thereof.
[0089] [Adhesive layer]
[0090] The adhesive composition described above can be used to form an adhesive layer. Sometimes, the adhesive layer formed using the adhesive composition of the present invention is referred to as the "adhesive layer of the present invention." The adhesive layer described above can be produced, for example, by applying the adhesive composition to the release surface of a release liner or a substrate to form an adhesive composition layer, and then curing the adhesive composition layer by solvent removal using heating or polymerization using radiation irradiation.
[0091] The aforementioned adhesive layer can be an adhesive layer that cures upon exposure to radiation (radiation-curing adhesive layer), or an adhesive layer that does not cure upon exposure to radiation (non-radiation-curing adhesive layer). Examples of such radiation include electron beams, ultraviolet rays, alpha rays, beta rays, gamma rays, or X-rays.
[0092] The adhesive layer of the present invention is preferably a sheet-like pressure-sensitive adhesive (solvent-free adhesive sheet) formed from a solvent-free adhesive composition. Therefore, the adhesive layer (solvent-free adhesive composition) of the present invention preferably contains at least a photopolymer as the base polymer. A photopolymer is a polymer formed by a polymerization method that utilizes radiation such as ultraviolet light to induce a polymerization reaction of polymerizable components.
[0093] The coating (coating) of the above-mentioned adhesive composition can be performed using known coating methods. For example, a gravure roller coater, a reverse roller coater, a licking roller coater, an dip roller coater, a bar coater, a doctor blade coater, a spray coater, a comma doctor blade coater, a direct coater, and other coating machines can be used.
[0094] From the viewpoint of ensuring sufficient adhesion to the adhered object, the thickness of the adhesive layer of the present invention is preferably 5 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more. From the viewpoint of reducing the thickness of the device used, the thickness of the adhesive layer of the present invention is preferably 300 μm or less, more preferably 200 μm or less, even more preferably 100 μm or less, and even more preferably 70 μm or less.
[0095] [Adhesive sheet]
[0096] Adhesive sheets can be obtained using the adhesive layer of the present invention. Sometimes, an adhesive sheet having the adhesive layer of the present invention is referred to as an "adhesive sheet of the present invention." The aforementioned adhesive sheet can be a double-sided adhesive sheet with adhesive layer surfaces on both sides, or a single-sided adhesive sheet with adhesive layer surfaces on only one side. From the viewpoint of bonding two components together, a double-sided adhesive sheet is preferred. It should be noted that in this specification, the term "adhesive sheet" also includes strip-shaped adhesive sheets, i.e., "adhesive tape." Furthermore, in this specification, the adhesive layer surface is sometimes referred to as the "adhesive surface."
[0097] The aforementioned adhesive sheet can be a so-called "substrate-free" adhesive sheet (hereinafter, sometimes referred to as "substrate-free adhesive sheet") that does not have a substrate (substrate layer), or it can be an adhesive sheet with a substrate (hereinafter, sometimes referred to as "substrate-supported adhesive sheet"). Examples of the aforementioned substrate-free adhesive sheets include, for instance, double-sided adhesive sheets containing only the adhesive layer of the present invention, and double-sided adhesive sheets containing the adhesive layer of the present invention and an adhesive layer other than the adhesive layer of the present invention (sometimes referred to as "other adhesive layers"). On the other hand, examples of substrate-supported adhesive sheets include adhesive sheets having the adhesive layer of the present invention on at least one side of the substrate. Among these, substrate-free adhesive sheets (substrate-free double-sided adhesive sheets) are preferred, and substrate-free double-sided adhesive sheets containing only the adhesive layer of the present invention are more preferred. Furthermore, adhesive sheets having adhesive layers on both sides of the substrate (substrate-supported double-sided adhesive sheets) are also preferred. The adhesive layers on both sides of the aforementioned substrate-supported double-sided adhesive sheet can both be the adhesive layer of the present invention, or one can be the adhesive layer of the present invention and the other can be another adhesive layer. It should be noted that the aforementioned "substrate (substrate layer)" does not include the release liner that is peeled off when using (adhering) the adhesive sheet.
[0098] The aforementioned substrate is an element that functions as a support for the adhesive layer in the aforementioned adhesive sheet. Examples of substrates include plastic substrates (especially plastic films). The aforementioned substrate can be a single layer or a laminate of the same or different types of substrates.
[0099] There are no particular limitations on the aforementioned substrates; examples include various optical films such as plastic films, anti-reflective (AR) films, anti-glare (AG) films, polarizing plates, and phase retardation plates. Examples of raw materials for the aforementioned plastic films include polyester resins such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose (TAC), polysulfone, polyarylate, polyimide, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene copolymer, cyclic olefin polymers such as "ARTON" (a cyclic olefin polymer manufactured by JSR Corporation) and "ZEONOR" (a cyclic olefin polymer manufactured by Zeon Corporation), and fluorinated polymers. It should be noted that only one of these plastic materials may be used, or two or more may be used.
[0100] To improve adhesion and retention with the adhesive layer, the surface of the substrate having the adhesive layer can be subjected to physical treatments such as corona discharge treatment, plasma treatment, sandblasting matte finish, ozone exposure treatment, flame exposure treatment, high voltage electric shock exposure treatment, and ionizing radiation treatment; chemical treatments such as chromic acid treatment; and surface treatments such as easy-to-adhere treatment using a coating agent (primer). Surface treatments to improve adhesion are preferably applied to the entire surface of the substrate on the adhesive layer side.
[0101] The aforementioned adhesive sheet may have release liner provided on the adhesive surface until use. The release liner protects the adhesive surface it contacts until the adhesive layer is used, and is then peeled off. It should be noted that when the adhesive sheet is a double-sided adhesive sheet, each adhesive surface may be protected by two separate release liners, or by a single release liner with both sides as release surfaces, wound into a roll. The release liner serves as a protective material for the adhesive layer and is peeled off when attached to the substrate. Furthermore, when the adhesive sheet is a substrate-free adhesive sheet, the release liner also functions as a support for the adhesive layer. It should be noted that a release liner may not be necessary.
[0102] Examples of substrates for the aforementioned release liner include: polyethylene film, polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polyethylene naphthalate film, polybutylene terephthalate film, polyurethane film, ethylene vinyl acetate film, ionomer resin film, ethylene-(meth)acrylate copolymer film, ethylene-(meth)acrylate copolymer film, polystyrene film, polycarbonate film, polyimide film, and fluorinated resin film. Cross-linked films of these materials can also be used. Furthermore, laminated films of these materials can also be used.
[0103] It is preferable to perform a peeling treatment on the peeling surface of the aforementioned release liner (especially the surface in contact with the aforementioned adhesive layer). Examples of release agents used in the peeling treatment include alkyd, polysiloxane, fluorinated, unsaturated polyester, polyolefin, and wax-based release agents.
[0104] There is no particular limitation on the thickness of the aforementioned release liner, for example, it is about 20 μm to about 150 μm.
[0105] Figure 1 This is a schematic cross-sectional view illustrating one embodiment of the adhesive sheet of the present invention. Figure 1 The adhesive sheet 1 shown is a substrate-free double-sided adhesive sheet containing a single layer of adhesive layer 2, which is the adhesive layer of the present invention, and release liner 3 and release liner 4 are respectively provided on its two adhesive surfaces.
[0106] [use]
[0107] The adhesive composition, adhesive layer, and adhesive sheet of the present invention are preferably used for optical applications, i.e., for bonding to optical components. More specifically, for example, for bonding optical components (optical component bonding applications), and for manufacturing articles using the aforementioned optical components (optical articles). Using the adhesive composition, adhesive layer, and adhesive sheet of the present invention for optical applications results in excellent reliability.
[0108] The adhesive layer and adhesive sheet of the present invention are used, for example, in optical components such as electrical and electronic devices, to assemble (install) various components or parts to designated locations (e.g., housings, front panels, window portions, etc.). It should be noted that "electrical and electronic devices" refers to devices that are at least one of electrical or electronic equipment. Examples of such electrical and electronic devices include, for example, image display devices such as liquid crystal displays, organic / inorganic electroluminescent displays, and plasma displays, as well as portable electronic devices. Examples of such image display devices include, for example, image display devices among the aforementioned portable electronic devices, vehicle-mounted displays, and digital signage (electronic billboards / electronic bulletin boards). It should be noted that the aforementioned image display devices can be of a so-called "rigid" or "flexible" form (structure), and can also be of a form (structure) capable of being bent or folded, such as a so-called "foldable" or "rollable" form.
[0109] Examples of portable electronic devices mentioned above include: mobile phones, smartphones, tablet PCs, laptop PCs, various wearable devices (such as wristwatches, modular devices worn on the wrist with clips or straps, eyewear (including monocular, binocular, and headband types), clothing devices worn as accessories on shirts, socks, hats, etc., and earwear such as headphones), digital cameras, digital camcorders, audio equipment (portable music players, digital voice recorders, etc.), computers (desktop calculators, etc.), portable game consoles, electronic dictionaries, electronic notebooks, e-books, in-vehicle information devices, portable radios, portable televisions, portable printers, portable scanners, portable modems, etc. It should be noted that in this specification, "portable" is not simply defined as being able to carry, but rather as having a level of portability that allows a standard adult to handle it relatively easily.
[0110] The adhesive composition, adhesive layer, and adhesive sheet of the present invention exhibit excellent flexural resistance at low temperatures. Therefore, even when used in areas subject to repeated bending at low temperatures, breakage, creases, or peeling of the adhesive sheet at the bending points are less likely to occur. Therefore, the adhesive sheet of the present invention is preferably used in areas subject to repeated bending. Therefore, the adhesive composition, adhesive layer, and adhesive sheet of the present invention are preferably used for bonding components (particularly between components) in electrical and electronic equipment used for bending, such as electrical and electronic equipment having a bendable image display device (flexible display) (especially a foldable image display device (foldable display)).
[0111] The embodiments described above are for the purpose of making the present invention easier to understand, and are not intended to limit the present invention.
[0112] Example
[0113] The following examples illustrate the present invention in more detail, but the present invention is not limited to these examples. It should be noted that the proportions (parts by mass) shown in Table 1 represent the proportions of each listed component.
[0114] Example 1
[0115] (Preparation of the prepolymer composition)
[0116] In a flask, 0.05 parts by weight of 2,2-dimethoxy-1,2-diphenylethane-1-one (trade name "Omnirad 651", manufactured by IGM Resins) and 0.05 parts by weight of 1-hydroxycyclohexylphenyl ketone (trade name "Omnirad 184", manufactured by IGM Resins) as a first photopolymerization initiator and 0.05 parts by weight of 1-hydroxycyclohexylphenyl ketone (trade name "Omnirad 184", manufactured by IGM Resins) as a second photopolymerization initiator were added to a monomer mixture containing 54 parts by weight of 2-hexyldecyl acrylate (2HDA), 35 parts by weight of lauryl acrylate (LA), and 11 parts by weight of 4-hydroxybutyl acrylate (4HBA). The mixture was then irradiated with ultraviolet light under a nitrogen atmosphere, thereby polymerizing a portion of the polymerizable components in the mixture, resulting in a prepolymer composition (containing unpolymerized polymerizable components) with a polymerization rate of about 10%.
[0117] (Preparation of the adhesive composition)
[0118] An adhesive composition was prepared by mixing 100 parts by weight of the above prepolymer composition, 0.06 parts by weight of dipentaerythritol hexaacrylate (DPHA) as a crosslinking agent, and 0.3 parts by weight of silane coupling agent (product name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.).
[0119] (Formation of the adhesive layer)
[0120] While the long first release liner is being moved along its length, the coating process, the first lamination process, the UV curing process, the release process, the heating process, and the second lamination process (roll-to-roll process) are performed sequentially. The first release liner is a 75 μm thick polyethylene terephthalate (PET) film with polysiloxane release treatment on one side. The travel speed of the first release liner is set to 4.0 m / min.
[0121] In the coating process, the adhesive composition described above is applied to the release-treated surface of the first release liner using a roller coater to form a coating film. In the first lamination process, the release-treated surface of a second release liner, which has undergone polysiloxane release treatment on one side, is laminated onto the coating film on the first release liner. The second release liner is a long PET film (75 μm thick) that has undergone polysiloxane release treatment on one side.
[0122] In the UV curing process, the coating between the release liner layers is irradiated with ultraviolet (UV) light to cure it, thus forming an adhesive layer with a thickness of 50 μm. A black light lamp is used as the irradiation source, and the irradiation intensity is set to approximately 6.5 mW / cm². 2 The cumulative irradiation intensity was set to 1200 mJ / cm. 2 .
[0123] In the peeling process, the second release liner is peeled off from the adhesive layer on the first release liner. In the heating process, first heating and second heating are performed sequentially in a hot air heated oven to dry the adhesive layer on the first release liner. In the first heating, the heating temperature (first heating temperature) is set to 120°C. In the second heating, the heating temperature (second heating temperature) is set to 90°C.
[0124] In the second bonding process, the release-treated side of a third release liner, which has undergone polysiloxane release treatment on one side, is bonded to the adhesive layer on the first release liner. The third release liner is a long PET film (75 μm thick) that has undergone polysiloxane release treatment on one side.
[0125] Through the above operations, an adhesive sheet with a double-sided release liner as described in Example 1 was produced.
[0126] Examples 2-3, Comparative Examples 1-4
[0127] In the preparation of the prepolymer composition, the monomer composition was changed as shown in Table 1. Otherwise, the adhesive layers and adhesive sheets of each example were prepared in the same manner as in Example 1. It should be noted that in Table 1, "2EHA" represents 2-ethylhexyl acrylate, "NOAA" represents n-octyl acrylate, and "2EHCA" represents 2-ethylhexyl carbitol acrylate.
[0128] <Evaluation>
[0129] The adhesive sheets of the embodiments and comparative examples were evaluated as follows. The evaluation results are shown in the table.
[0130] (1) Shear storage modulus
[0131] A necessary number of test samples were prepared for each adhesive sheet. Specifically, firstly, multiple small pieces of adhesive sheet cut from the adhesive sheet were glued together to create a sample sheet with a thickness of approximately 1.0 mm. Next, this sheet was punched to obtain cylindrical particles (7.9 mm in diameter) for use as test samples. Then, for the test samples, dynamic viscoelasticity measurements were performed using a dynamic viscoelasticity measuring device (product name "Discovery Hybrid Reometeter-2 (DHR-2)", manufactured by TA Instruments, fixed to a clamp with a parallel plate of 7.9 mm diameter. In this measurement, the measurement mode was set to shear mode, the measurement temperature range was set to -50℃ to 150℃, the heating rate was set to 5℃ / min, and the frequency was set to 1Hz. The shear storage modulus at specified temperatures (-20℃, 25℃) was read from the measurement results.
[0132] (2) Initial haze value
[0133] The first release liner is peeled off from the adhesive sheet, exposing one adhesive surface. The exposed adhesive surface is then bonded to a glass plate (0.55 mm thick, haze value 0.1%). The third release liner is then peeled off, exposing the other adhesive surface. The glass plate (0.55 mm thick, haze value 0.1%) is then bonded to the exposed adhesive surface, thus creating a laminated sample comprising [glass plate / adhesive sheet / glass plate]. The laminated sample was then measured at room temperature (23°C) using a haze measuring device (trade name "HR-100", manufactured by Murakami Color Research Institute Co., Ltd.). The measurement was repeated three times, and the average value was taken as the initial haze value.
[0134] (3) Haze value after damp heat test
[0135] The laminated sample prepared for the initial haze value determination was stored at 65% temperature and 90% RH for 500 hours. It was then removed and allowed to stand at room temperature (23°C). The haze value was then measured in the same manner as the initial haze value determination. This was repeated three times, and the average value was taken as the haze value after the damp heat test. Furthermore, the difference in haze values before and after the damp heat test, ΔHz (haze value after damp heat test - initial haze value), was calculated.
[0136] (4) Dielectric constant (relative permittivity)
[0137] The dielectric constant of the adhesive sheets used in the examples and comparative examples was measured as follows. The dielectric constant of the adhesive sheets was measured using the adhesive surface exposed after the third release liner was peeled off from the obtained adhesive sheets as the measurement surface.
[0138] The sample was prepared by sandwiching it between a copper foil and an electrode. Then, the dielectric constant of the sample was determined under the following conditions using a Precision Impedance Analyzer 4294A manufactured by Agilent Technologies, according to JIS K6911.
[0139] [Conditions for determining dielectric constant]
[0140] Electrode composition: Aluminum plate with a diameter of 12.1 mm and a thickness of 0.5 mm.
[0141] Counter electrode: 3oz copper plate
[0142] Measurement environment: Temperature 25℃, relative humidity 50%
[0143] Frequency: 100kHz
[0144] Table 1
[0145] As shown in Table 1, the adhesive sheet of the embodiment has a low shear storage modulus at -20°C, thus exhibiting excellent flexural resistance in the low-temperature region. Furthermore, it has a small ΔHz, indicating it is less prone to clouding over time. In contrast, Comparative Examples 1, 3, and 4 have high shear storage modulus at -20°C, indicating poor flexural resistance in the low-temperature region. Additionally, Comparative Example 2 has a large ΔHz, indicating it is prone to clouding over time.
[0146] The following describes variations of the invention.
[0147] [Appendix 1] An adhesive composition, wherein the adhesive composition is an adhesive composition with a shear storage modulus (G') of less than 60 kPa at -20°C, and regarding a laminate obtained by bonding two pieces of glass together using the adhesive composition, the difference ΔHz between the haze value of the laminate after the damp heat test and the initial haze value of the laminate before the damp heat test [haze value after damp heat test (%) - initial haze value (%)] is less than 2% after the damp heat test.
[0148] [Note 2] According to the adhesive composition described in Note 1, the shear storage modulus (G') of the adhesive composition at 25°C is 40 kPa or less.
[0149] [Note 3] The adhesive composition according to Note 1 or 2, wherein the initial haze value is greater than 0.01% and less than 3%, and the haze value after the damp heat test is greater than 0.01% and less than 4%.
[0150] [Note 4] The adhesive composition according to any one of Notes 1 to 3, wherein the dielectric constant of the adhesive composition at a frequency of 100 kHz is 4.0 or less.
[0151] Label Explanation
[0152] 1. Adhesive sheet
[0153] 2 Adhesive layer
[0154] 3, 4 Peeling the gasket
Claims
1. An adhesive composition, wherein, The adhesive composition is an adhesive composition with a shear storage modulus (G') of less than 60 kPa at -20°C. Regarding the laminate obtained by bonding two pieces of glass together using the adhesive composition, after a damp heat test in an environment of 65°C and 90%RH for 500 hours, the difference ΔHz between the haze value of the laminate after the damp heat test and the initial haze value of the laminate before the damp heat test [haze value after damp heat test (%) - initial haze value (%)] is less than 2%.
2. The adhesive composition according to claim 1, wherein, The shear storage modulus (G') of the adhesive composition at 25°C is below 40 kPa.
3. The adhesive composition according to claim 1 or 2, wherein, The initial haze value is greater than 0.01% and less than 3%, and the haze value after the damp heat test is greater than 0.01% and less than 4%.
4. The adhesive composition according to claim 1 or 2, wherein, The dielectric constant of the adhesive composition is 4.0 or less at a frequency of 100 kHz.
Citation Information
Patent Citations
Adhesive double coated sheet and method of affixing touch panel to display device
JP2003238915A
Double-sided adhesive sheet and display device with touch panel
JP2003342542A
Pressure sensitive adhesive double-sided sheet and display device with touch panel
JP2004231723A
Adhesive sheet
JP2018111754A